2022
DOI: 10.1155/2022/9104209
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Correlation of D-Dimer Levels with COVID-19 Severity: A Scoping Review

Abstract: Aims. The review explores the findings of previous studies to elucidate the association between levels of D-dimer and COVID-19 severity and prognosis. In addition, we assessed the efficiency of anticoagulant therapies in reducing COVID-19 severity and improving the prognosis of the patients. Materials and Methods. A comprehensive literature review was conducted using MEDLINE/PubMed databases, Scopus, and Web of Science with the help of keywords “COVID-19,” “D-Dimer,” “Thrombosis,” “Fibrin network,” “Anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…11 Several retrospective studies report that d-dimer levels are associated with the disease severity and mortality in COVID-19. 12 The hallmark of the lung damage in COVID19 is intraalveolar fibrin deposition. d-dimer is a protein degradation product of fibrin that is formed by plasmin during fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Several retrospective studies report that d-dimer levels are associated with the disease severity and mortality in COVID-19. 12 The hallmark of the lung damage in COVID19 is intraalveolar fibrin deposition. d-dimer is a protein degradation product of fibrin that is formed by plasmin during fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies report that the lungs are the potential sources of d-dimer in COVID-19. [11][12][13] A retrospective study from Wuhan, China reports the COVID-19 outcome from 676 laboratory-confirmed cases. The study comes from the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations